Remaining steps to Memorial Hall at Salem College, after the demolition of the building, 1965. - (:unkn) unknown (Forsyth County Public Library, 2008)
WSJ 12-19-65 p.A8.
Remaining steps to Memorial Hall at Salem College, after the demolition of the building, 1965.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth